2003
DOI: 10.1161/01.hyp.0000103161.27190.67
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Chromosome 1 Region Affecting Blood Pressure and Vascular Disease Traits in the Stroke-Prone Rat Model

Abstract: Abstract-Recently, a genome-wide screen has shown a major quantitative trait locus (QTL) for a stroke-associated phenotype on rat chromosome 1 (RNO1) independent of QTL for blood pressure (BP) in the stroke-prone spontaneously hypertensive rat (SHRSP) of a Heidelberg colony. However, it remains to be elucidated whether these observations reflect the existence of different genes predisposing to each of the disorders. To address this issue, we performed comprehensive approaches in a Japanese colony, Izm, as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
3
35
1
Order By: Relevance
“…Our study clearly illustrated a major effect of the chr-1 QTL on this phenotype, which was independent of the genetic background. This contrasted well with the case of BP per se; in the adult congenic strains, BP was only marginally different between WKYpch1.0 and WKY (7,22), but was significantly lower in SHRSPwch1.0 compared to SHRSP (11,12). This means that BP is a more "remote" phenotype under more complex control by a number of genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 62%
“…Our study clearly illustrated a major effect of the chr-1 QTL on this phenotype, which was independent of the genetic background. This contrasted well with the case of BP per se; in the adult congenic strains, BP was only marginally different between WKYpch1.0 and WKY (7,22), but was significantly lower in SHRSPwch1.0 compared to SHRSP (11,12). This means that BP is a more "remote" phenotype under more complex control by a number of genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 62%
“…[25][26][27] Simultaneously, our search of intermediate phenotypes indicated sympathetic hyper-responsiveness to stresses in the congenic strains constructed for this QTL. [28][29][30] A follow-up study using preparations of isolated neonatal brain stem confirmed that the electrophysiological nature of neurons in the rostral ventrolateral medulla, one of the most important centers for sympathetic activity regulation, were influenced by the Chr 1 QTL, suggesting that rostral ventrolateral medulla is one of the primary targets of the gene(s) in this QTL.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 86%
“…On RNO1 several QTLs linked to BP, 47,48,54,77,90,[177][178][179][180][181][182][183] stroke or strokeassociated phenotypes, 182,184 and renal damages 48,54,77,90,141,142,151 could be identified in different rat models. To demonstrate genetic differences in the incidence of hypertension, cerebral stroke and renal damage under salt loading in tap water (1% NaCl), Ishikawa et al 185 analysed five congenic rat strains, in which different chromosomal segments from WKY/Izm-RNO1 were transferred into the SHRSP/ Izm background ( Table 2).…”
Section: Consomic Studiesmentioning
confidence: 99%